The Effect Of Landscape Slope On Soil Organic Carbon In Liberec District In The Czech Republic - Shahin Nozari, Luboš Borůvka (International Journal of Advanced Science and Technology, 2020)
The largest global stock of organic carbon (C) on land is contained in soils (2500 Pg of C to 2 - m depth) and is about twice as large as the atmospheric C stock. Soil properties such as SOC are used to indicate soil ability to store the nutrients and water needed for plant growth. The distribution of SOC is influenced by topography and land-use. In this study, we analyzed the relationship between SOC and slope in topsoils of the Liberec region of the Czech Republic. Topsoil samples were randomly collected in Liberec (n = 69). Linear regression was performed to analyze the relationships between slope and SOC stock. Correlation matrices were performed to determine various relationships between selected variables (e.g. SOC, slope, etc.). The relationship of SOC and slope was positive though relatively weak (R2 = 0.28, p ≤ 0.05). Generally, all parameters relating to the slope such as relative position on the slope (RSP) and the slope length factor (LSF) were positively correlated. Since the results of the relationship between SOC and slope were very weak, we divided the region’s data by land use (arable land, complex systems of cultures and parcels, and forests). For arable land, the relationship of SOC and slope was positive (R2 = 0.35), for complex systems it was stronger than others (R2 = 0.59), and for forests it was very week (R2 = 0.13). The results show that separating the data observed had a positive effect on increased R2 results in the relationship between SOC and slope. It indicates that the processes controlling the distribution of SOC along the slopes differ between the land-use types.